How big is the gig? Assessing the preliminary evidence on the effects of digitalization on the labor market - Werner Eichhorst; Holger Hinte; Ulf Rinne; Verena Tobsch (Institute for the Study of Labor (IZA), 2016)
This paper assesses the importance of digitalization in Germany and other developed countries with a particular attention to the potential or actual impact it may have on the labor market. Referring to available empirical evidence, we document the already developing transformation of occupations and forms of employment and the role of the platform economy, including the phenomenon of solo self-employment. We then derive current and future challenges for social protection and suggest some ideas to update social insurance in the face of these new challenges.
Keywords: J08; J24; O33; O38; 330; digitalization; robots; automation; future of work; industry 4.0; technical changes; sharing economy; platform economy; labor market; welfare state